PENERAPAN MODEL PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION (RME) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 173 PEKANBARU - Mukhtar, Nursalmi (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
This study was conducted in SD Negeri 173 Pekanbaru at class V with 36 students, consisting of 19 male students and 17 female student. Based on preliminary observations V graders learnt mathematics that is still low than KKM (Complete Minimal Criteria) 70 average grade was 66.90 with 42.5 % completeness percentage. To solve this problem researchers tried to apply Contextual Learning Approach to improve students achievement on mathematics at class VB SD Negeri 43 Pekanbaru. The metdhod used was a Classroom Action Research (CAR), which consists of 2 cycles. The first cycle consists of 2 meetings and the second cycle consists of 2 meetin. The research instrument consisted of learning devices (syllabi, lesson plan, worksheets, and achievement test sheets), teacher observation sheets and student activities sheet. The research data were analyzed descriptively. Results of this study indicated that the student achievement has increased, the teacher activity of the first meeting 65 % and the second meeting of the first cycle was 73 %, mean while the teachers avtivity from the second meeting on the first cycle to the meeting of the second cycle increased to the 90 % and than it is increase to 96 % from the first meeting to the second meeting of second cycle. While the students activity of the first meeting of the first cycle of was 60 %, and the second meeting of the first cycle increased to 71 %. Then it increas to 83 % from the second meeting of the first cycle to the first meeting of the second cycle, and increase to 94% from the first meeting of the second cycle to the second meeting of the second cycle. There were increasing of student achievement from the mean score, 66.9 to 72.88 in cycle first, and it increased 75.6 to the second cycle. It can be concluded that the implementation contextual approach could improve students mathematics student achievement at V class of SD Negeri 173 Pekanbaru.